Influence of chewing gum containing natural host proteins with antimicrobial properties on saliva in subjects with hyposalivation - Pillay, Thanusha Devi (My University, 2014)
Biotène® products have been developed with the intention of preventing tooth decay, plaque accumulation and oral infections in individuals with xerostomia (dry mouth). Not much is known about the effect of Biotène® chewing gums. Biotène® chewing gum contains host proteins. Due to these contents the manufacturer claims that Biotène® chewing gum is an “enzyme gum” that “boosts and strengthens the mouths natural defences”. The aim of this study was to investigate the effect of Biotène® chewing gum on saliva flow rates, saliva buffering capacity, plaque index, as well as salivary Streptococcus mutans and Lactobacilli counts, in healthy subjects with hyposalivation. One hundred and nine subjects with an age range of 18 to 23 years were screened for hyposalivation. Hyposalivation is a reduced salivary flow rate in a subject based on examination of the subject. Thirteen healthy subjects, who initially presented with hyposalivation, were included in the study. A baseline laboratory analysis of saliva was performed. Saliva was collected at rest and with masticatory stimulation, and measured. Resting saliva is saliva produced without any stimulation and can be obtained by allowing the subject to passively drool into a sputum jar. Stimulated saliva is produced as a result of stimulation of the salivary glands and may be obtained by allowing subject to chew inert rubber tubing while expectorating into a sputum jar. Buffering capacity was performed on both the saliva samples. Plaque index and DMFT was measured. Bacterial counts such as S. mutans and Lactobacilli counts were performed on the stimulated saliva. Subjects were given rubber tubing, xylitol chewing gum or Biotène® chewing gum to use for 2 weeks. A rubber tubing phase was introduced into the study to eliminate the effect of masticatory stimulation, which any chewing gum can provide. A xylitol-containing chewing gum (xylitol) phase was also introduced into the study in order to eliminate the effect of xylitol, as Biotène® chewing gum contains xylitol. A second laboratory analysis of saliva was performed. After a two weeks wash out period the second test product was given and the same procedure was repeated with the third product. The results showed that two weeks use of Biotène® chewing gum had no significant effect on the resting and stimulated saliva flows. It did not increase the buffering capacity of either the resting or stimulated saliva samples. Although it did not reduce the plaque index and S. mutans counts, it significantly reduced the Lactobacilli counts. Xylitol chewing gum, which was used as a control to eliminate the xylitol effect from the Biotène® chewing gum, significantly increased the stimulated saliva, reduced the plaque index and the salivary Lactobacilli count. Biotène® chewing gum which contains host proteins has no beneficial effects regarding saliva flow rate or against dental plaque and therefore against dental caries.
Keywords: Tooth Diseases--prevention & control